Bimbingan Teknis Metode Empatik di Masa Pandemi terhadap Calon Guru Bimbingan dan konseling (BK) di Lingkungan Lembaga Pendidikan (LP) Ma’arif Kota Metro Lampung - Hernisawati Hernisawati; Kushendar Kushendar; Habib Shulton A.; Farhana Sabri; Firman Nur Hidayat; Aprezo Pardodi Maba; Muh. Ngali Zainal Makmun (Kuras Institute & Scidac Plus, 2022)
Distance learning activities are the only encouragement for elementary school teachers to make interesting strategies in the learning process, the use of learning media is one of the teachers in order to be able to create interesting activities and so that students are expected to be able to follow the learning process carefully without complaints, because good learning using learning media. The purpose of this activity is a form of community service in the form of assisting learning media using the Canva application. The method of activity carried out is service learning with the subject of the activity, namely inviting all elementary school teachers in Makati Jaya, to take advantage of the Canva application. The Canva application is a platform that can be accessed by anyone using a smartphone or using a computer browser. This assistance provides an overview for teachers to take advantage of free applications that can be used to create interesting and not monotonous learning media by utilizing these applications.